The Algorithm Of Giving Automatic Harakat On Arabic Script Without Harakat Using Cyclomatic Complexity Testing - Qudsi, Dini Hidayatul; Saf, Maksum Ro’is Adin (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The majority of Arabic reference books in Arabic writing without a vowel/harakat cause students to have difficulty in learning Arabic. Reading Arabic Script without harakat requires an understanding of the science of Nahwu-Sharf (Arabic Grammar) to be able to understand its contents. Therefore, in this study the science of Nahwu-Sharf has been translated into an algorithm that can be used to provide an automatic harakat on Arabic script (without harakat). The generated algorithm has been examined using cyclomatic complexity and results in accordance with Nahwu-Sharf science, through an 9-path test case examination. It means that the algorithm is assumed to be well-structured, highly testable and maintainable. Keywords : Arabic, Harakat, Nahwu-Sharf, Algorithm, and Cyclomatic Complexity Testing.